The Role of Migrant Parents in Shaping Students’ Religious Attitudes - Mushthafiyah, Syifa' Nuril; Jailani, Abd. Qadir; Hidayatullah, Moh. Wildan (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
The role as a parent is a responsibility and obligation carried out by parents to their children, namely in educating and shaping the character and attitude of children to be religious. This study aims to explore how religious education of migrant parents to their children who study at MTs An-Najah and explore the supporting and inhibiting factors. This study uses a descriptive qualitative method. The data sources in this study are migrant parents, homeroom teachers and school teachers. Data collection uses interviews, observations, and documentation. In the data analysis technique using data reduction, data presentation, and drawing conclusions and to check the validity of the data using source triangulation by comparing the results of interviews with several informants. The results of this study are that the role of migrant parents in shaping students’ religious attitudes, (1) Instilling good behavior in children from an early age (2) Accustoming children to be disciplined about time, such as worship, playing and studying (3) Providing guidance at all times regarding ethics to others, especially to those who are older. While the supporting factors consist of substitute families, parents, teachers and Islamic boarding schools. Meanwhile, inhibiting factors consist of distance and time with parents who live away from home and factors within the child themselves.